The influence of wall conditioning procedures on outgassing rate of stainless-steel in the “Uragan-2M” torsatron - Glazunov, G.P.; Baron, D.I.; Bondarenko, M.N.; Chernyshenko, V.Ya.; Konotopskiy, A.L.; Listopad, V.M.; Maznichenko, S.M.; Pashnev, V.K. (Вопросы атомной науки и техники, 2012)
Using the thermal desorption method the investigations were carried out of stainless steel probe outgassing rate in a vacuum and estimation of the number of monolayers on its surface in the Uragan-2M torsatron in situ. The decrease of surface impurity by more than one order of magnitude was measured at the vacuum improvement from 1.6·10⁻⁶ Torr up to 6.5·10⁻⁷ Torr after pumping and RF discharge cleaning. Mass-spectrometric measurements has shown H₂O (18 m/e), Co₂ (44 m/e) and 28 m/e (CO+N₂), as the main gases desorbed from probe surface during its heating. Heavy hydrocarbon masses (58 m/e) were also registered. Some practical conclusions were made for the U-2M wall conditioning procedure improvement. Термодесорбционным методом проведены исследования газовыделения нержавеющей стали и оценка числа монослоев примесей на ее поверхности в торсатроне Ураган-2М. После откачки и чистки ВЧ-разрядами количество примесей снизилось более чем на порядок при улучшении вакуума с 1.6·10⁻⁶ до 6.5·10⁻⁷ Торр. Масс- спектрометрические измерения показали, что основными примесями, десорбирующимися с поверхности зонда из нержавеющей стали во время его нагрева до температуры 250…300 ºС, являются: H₂O (18 m/e), Co₂ (44 m/e) и 28 а.е.м. (CO+N₂). Тяжелые углеводороды (58 а.е.м.) также регистрируются. Сделаны некоторые практические заключения для улучшения процедуры чистки стенок камеры торсатрона Ураган-2М. Термодесорбційним методом проведено дослідження газовиділення нержавіючої сталі і оцінка числа моношарів домішок на її поверхні в торсатроні Ураган-2М. Після відкачування і чищення ВЧ-розрядами кількість домішок знизилася більш ніж на порядок при поліпшенні вакууму з 1.6·10⁻⁶ до 6,4·10⁻⁷ Торр. Мас- спектрометричні вимірювання показали, що основними домішками, що десорбуються з поверхні зонда з нержавіючої сталі під час його нагріву до температури 250…300 ºС, є: H₂O (18 а.е.м.), Co₂ (44 а.е.м.) i 28 а.е.м. (CO+N₂). Важкі вуглеводні (58 а.е.м.) також реєструються. Зроблені деякі практичні висновки для поліпшення процедури чищення стінок камери торсатрона Ураган-2М.